Validation Method of Flame-AAS with Microwave Digestion for Mineral Analysis in Carbohydrate-Rich Samples - Imas Solihat; Didah Nur Faridah; Nancy Dewi Yuliana (Molekul, 2018)
One of the effective methods for mineral destruction is by using microwave digestion. However, some parameters in the microwave manual book are different with AOAC method such as the volume of acid, temperature, and the length of destruction time (Δt). Thus, a validation for mineral analysis method of Fe, Zn, and Cu by using microwave digestion method is required. In this study, carbohydrate-rich samples such as rice and canned pineapple were being used for the validation of mineral analysis method of Fe, Zn, and Cu using microwave digestion. The parameters of this research include LOD, LOQ, LDM, linearity, precision, accuracy, and reproducibility. The accuracy result for Fe, Zn, and Cu mineral was found in the range of 75-120% with good precision value (% RSD <% 2/3RSD Horwitz). Based on the results, accuracy for mineral Fe, Zn and Cu found in the range of 75-120% with good precision value (% RSD <% 2/3RSD Horwitz). The regression curves of the Fe, Zn, and Cu minerals gave the value of R2> 0.990. For LDM values in the rice samples consecutively for Fe, Zn, and Cu minerals were 0,06; 0,07; 0,04 mg/L, while for the canned pineapple were 0,07;0,10;0,01 mg/L, respectively. The results of a modified method for minerals Fe, Zn and Cu analysis in carbohydrate-rich samples was not significantly different from AOAC (2012). Thus the method was acceptable to be used in laboratory analysis.